2009
DOI: 10.3233/fi-2009-0041
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Universal One-dimensional Quantum Cellular Automata in Two Flavours

Abstract: We give a one-dimensional quantum cellular automaton (QCA) capable of simulating all others. By this we mean that the initial configuration and the local transition rule of any onedimensional QCA can be encoded within the initial configuration of the universal QCA. Several steps of the universal QCA will then correspond to one step of the simulated QCA. The simulation preserves the topology in the sense that each cell of the simulated QCA is encoded as a group of adjacent cells in the universal QCA. The encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 23 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…In the bounded-size configurations case, circuit universality coincides with intrinsic universality, as noted by Van Dam [37]. Intrinsically universal QCA in the one-dimensional case have also been resolved [2]. Finally, a subsequent work, which crucially builds upon the result of this paper, exhibits an n-dimensional intrinsically universal QCA [3].…”
Section: Qca: Simplification and Universalitysupporting
confidence: 63%
See 1 more Smart Citation
“…In the bounded-size configurations case, circuit universality coincides with intrinsic universality, as noted by Van Dam [37]. Intrinsically universal QCA in the one-dimensional case have also been resolved [2]. Finally, a subsequent work, which crucially builds upon the result of this paper, exhibits an n-dimensional intrinsically universal QCA [3].…”
Section: Qca: Simplification and Universalitysupporting
confidence: 63%
“…that they can all simulate each other in a space-preserving manner. The definition of intrinsic simulation has already been translated in the quantum context [2], however as it stands this is not sufficient to obtain the desired result. In this paper the definition of intrinsic simulation in the quantum context is discussed and developed, before the equivalence between all the various above-mentioned definitions of QCA is tackled.…”
Section: Qca: Simulation and Equivalencementioning
confidence: 99%
“…In the bounded-size configurations case, circuit universality coincides with intrinsic universality, as noted by Van Dam [49]. QCA intrinsic universality in the onedimensional case has been resolved [5], and also in the general n > 1-dimensional case [7]. Both results rely on recent work [6], where it was shown that a simple subclass of QCA, namely Partitioned QCA (PQCA), are intrinsically universal.…”
Section: Introductionmentioning
confidence: 73%
“…• Dimension three is particularly interesting, not only because of the relevance to physics, but because intrinsic universality QCA constructions lend themselves to a striking simplification. In dimension one the simplest known intrinsically universal QCA has cell dimension 36 [5]. In dimension two it has cell dimension 4 [7], and seems reducible to 3 via a costly and inelegant variation of the scheme [7], but probably no further.…”
Section: Introductionmentioning
confidence: 99%
“…that they can all simulate each other in a space-preserving manner. The definition of intrinsic simulation has already been translated in the quantum context [37], however as it stands this is not sufficient to obtain the desired result. In this paper the definition of intrinsic simulation in the quantum context is discussed and developed, before the equivalence between all the various above-mentioned definitions of QCA is tackled.…”
Section: Qca: Simulationmentioning
confidence: 99%